(untitled) (Baghdad Science Journal, 2025)
The present study is considered a pioneer investigation that deal with the terrestrial brown garden snail Cornu aspersum (Müller), in Iraq. Cornu aspersum however is considered an exotic species in many parts of the world ,The species is most probably infiltrates with plants transferred from one place to another. The species has gained importance in many ways. Nutritionally, the species is consumed as food item in many countries, but in other cases it is considered as pest for the damage it causes when feeding on valuable plant shoots. It also has medical importance for its role and ability in healing wounds, burns and remedy of other skin problems. This snail species however may act as a vector for some parasitic nematodes that cause serious diseases. The species is also important in scientific research, usually referred to as ‘ecological indicator’ employed in environmental pollution problems such as the one caused by heavy metals. A great deal of research on this species has been carried out in different parts of the world, however, in Iraq, the scientific attention given to land snails in general and to Cornu aspersum in particular is rare and may be negligible in comparison with the research carried out on aquatic Mollusca species. A total of 1880 individuals of Cornu aspersum were collected from all sampling sites. The study was carried out for the period November 2007 to November 2008 on three sites within the Jadiriya district in Baghdad.. Growth, size classes and shell dimensions of Cornu aspersum populations, and their relationship with major environmental factors; ambient temperature; soil pH, moisture, texture; and the soil content of organic matter have been also investigated. Identification of the species was confirmed by the British Natural History Museum.The data were analyzed by means of standard statistical procedures.